Virtual Gamification in a PBS-based SETA Program (Journal of The Colloquium for Information Systems Security Education, 2025)
The insider threat remains a significant concern in information security, with self-efficacy and protection motivation emerging as key factors influencing compliance. Security Education Training and Awareness (SETA) programs often address self-efficacy but fail to adequately enhance protection motivation. This paper adopts an educational perspective by incorporating Positive Behavior Support (PBS) pedagogy into a SETA framework, emphasizing the use of virtual gamification and PBS principles to foster a positive, engaging training environment. The proposed nomological model, designed for future testing, evaluates the effects of PBS, gamification, and virtualization on protection motivation and self-efficacy. To bridge the gap between theory and practice, this paper also discusses strategies for direct implementation of PBS-based gamification in organizational settings, such as positive reinforcement, incentivized participation, and adaptive training scenarios. These approaches allow organizations to address immediate security challenges while contributing valuable insights for refining the model. The implications of this research extend beyond compliance, offering a scalable methodology for creating a sustainable, positive organizational security culture.
Keywords: SETA; PM; SE; Gamification; Positive behavior support (PBS); XR; AR; VR; Information security (InfoSec)